2021
DOI: 10.1016/j.jcf.2020.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress in adults with and without cystic fibrosis during the COVID-19 lockdown

Abstract: Background: Hundreds of papers have been published on the COVID-19 pandemic, and several of them on psychological themes connected with it, but very little is so far known on how adult patients with Cystic Fibrosis (pwCFs) are coping with this dramatic event.Methods: An online questionnaire was developed according to the Italian validated COVID-19 Peritraumatic Distress Index (CPDI) and addressed to the general population (GP). A similar questionnaire, augmented with CF specific questions, targeted pwCFs. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 35 publications
(35 reference statements)
7
39
0
Order By: Relevance
“…Based on recent expertise during the pandemic [ 21 , 22 ], the survey was organized and managed according to previous methods used in survey studies by the authors. The present study aimed to investigate the psychological impact of the pandemic on front-line staff working at the new COVID-19 ward at Milano Fiera, Lombardy during the second pandemic wave.…”
Section: Introductionmentioning
confidence: 99%
“…Based on recent expertise during the pandemic [ 21 , 22 ], the survey was organized and managed according to previous methods used in survey studies by the authors. The present study aimed to investigate the psychological impact of the pandemic on front-line staff working at the new COVID-19 ward at Milano Fiera, Lombardy during the second pandemic wave.…”
Section: Introductionmentioning
confidence: 99%
“…As Italy became a COVID‐19 “hot spot,” concerns about the psychological functioning of pwCF increased. In a large study in Italy, an online questionnaire, the COVID‐19 Peritraumatic Distress Index, was completed in an adapted form by 712 pwCF and 3560 respondents from the general population 19 . Psychological distress in the mild to moderate range affected similar proportions of both samples; 40.2% of pwCF and 43.9% of the general population.…”
Section: Introductionmentioning
confidence: 99%
“…The sample size ranged from 48 to 13,829. Except for three studies [6,40,58] that did not report participants' ages, three studies reported median with interquartile range [41,44,46], and one study [53] reported range of age; all the remaining studies reported mean age. The most frequently used assessment tool was DASS-21 which was used in 7 studies [42,[48][49][50][51]53,55] measuring depressive symptoms, anxiety, and stress.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Of the 25 studies included, 17 [6,39,40,[43][44][45][46][48][49][50][51][53][54][55][56][57][58] were cross-sectional studies, and of the remaining studies, 6 [38,41,42,52,59,60] were case-control studies, and 2 [47,61] were longitudinal studies. Four studies [38,44,54,59] were conducted in Turkey, three in the United States [43,46,61], three in Spain [49][50][51] and Italy [53,55,58], two in Australia [40,48], China [39,56], and Iran [41,45], and one Germany [52], the Netherlands [60], Bangladesh [42], Israel [6], and Argentina ...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation